The Effectiveness of LingQ Application as Learning Media on the Student’s Reading Comprehension - Hayatun Nufus Rumaf; Agus Setiawan; Nursalim (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
Reading comprehension ability is one of the most important basic skills in learning English. However, the reality is that many junior high school students still struggle to understand reading texts, which is caused by limited vocabulary, monotonous teaching methods, and low learning motivation. Therefore, innovative and engaging learning media are needed, one of which is through the use of the LingQ application. This research aims to determine the effectiveness of using the LingQ application as a learning medium on the reading comprehension ability of eighth-grade students at Muhammadiyah Aimas Junior High School. This research uses a quantitative method with a pre-experimental design in the form of a one-group pre-test and post-test design. The research sample consisted of 20 students from class VIII B. The instrument used was a multiple-choice reading comprehension test with 20 questions. Data analysis techniques include descriptive statistical analysis, normality tests, and N-Gain tests. The research results indicate an effective in students' reading comprehension after being treated using the LingQ application. The average pre-test score was 48.00, which increased to 65.20 on the post-test. The N-Gain test results showed a value of 0.33, which falls into the moderate category, meaning that using the LingQ application is quite effective in students' reading comprehension.